2016
DOI: 10.1177/1557988316630952
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Education in African American Barbershops

Abstract: There have been very few studies to rigorously evaluate the potential of African-American barbers to educate men about prostate cancer (PCa) in the barbershop setting. This research brief presents baseline data from a cross-sectional survey identifying differences in decisional conflict and stage of decision making by screening status from an efficacy trial to educate African-American men about informed decision-making for prostate cancer screening. Those men who had already received the PSA test were more adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Some studies have shown that many African American men do not communicate well with their regular healthcare providers [25]. While shared decision making is recommended prior to PSA screening, several studies highlight that African American men may not be making informed decisions about PSA screening due to patients having low health literacy, knowledge about the test, and past history of receiving PSA [6,26,27]. Moreover, healthcare providers may not be offering sufficient up-to-date information or may not be asking patients about their preferences, thereby hindering the shared decision-making process [28].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that many African American men do not communicate well with their regular healthcare providers [25]. While shared decision making is recommended prior to PSA screening, several studies highlight that African American men may not be making informed decisions about PSA screening due to patients having low health literacy, knowledge about the test, and past history of receiving PSA [6,26,27]. Moreover, healthcare providers may not be offering sufficient up-to-date information or may not be asking patients about their preferences, thereby hindering the shared decision-making process [28].…”
Section: Discussionmentioning
confidence: 99%